Perceptions of climate change from North India - Kvanneid, Aase J. ([S.l.])
1 online resource
Keywords: Perceptions of Climate Change from North India: An Ethnographic Account explores local perceptions of climate change through ethnographic encounters with the men and women who live at the front line of climate change in the lower Himalayas. From data collected over the course of a year in a small village in an eco-sensitive zone in North India, this book presents an ethnographic account of local responses to climate change, resource management and indigenous environmental knowledge. Aase Kvanneid's observations cast light on the precarious reality of climate change in this region and bring to the fore issues such as access to water, NGO intervention and climate information for farmers. In doing so, she also explores classic topics in the study of rural India including ritual, gender, social hierarchy and political economy. Overall, this book shows how the cause and effect of climate change is perceived by those who have the most to lose and explores how the impact of climate change is being dealt with on a local and global scale. This book will be of great interest to students and scholars of the anthropology of climate change, environmental sociology and rural development.